Triassic-Jurassic carbonates from the Hochfelln Mountain (Northern Calcareous Alps) - Its facies, silicified fauna and implications for the end-Triassic biotic crisis - Seuß, Barbara; Höfling, Richard; Nützel, Alexander (Facies, 2005)
A suite of Early Mesozoic (Late Triassic, Norian to Early Jurassic) calcareous beds was studied from the Hochfelln Mountain in the Northern Calcareous Alps (NCA, South Germany). The Hauptdolomit Group consists of thick peritidal deposits and is overlain by basin deposits of the Rhaetian Kössen Formation and Rhaetian reefoidal limestone with corals. Unlike many other sections in the Tethys realm, coral growth seems to continue into the Jurassic or starts again relatively early within the Early Jurassic. Silicified corals and other marine invertebrates are present in the calcareous, micritic Hochfelln Beds. A re-examination of previously collected ammonite material indicates the presence of Coroniceras sp. which suggests an Early Sinemurian age for the Hochfelln Beds. Abundant sponge spicules (spiculites) suggest that sponges were the source for the silicification. The site produced one of the most diverse Early Jurassic (Sinemurian) gastropod faunas of the NCA (25-30 species, some undescribed). The relatively diverse Early Sinemurian gastropod fauna and coral growth indicate rapid recovery from the end-Triassic biotic crisis. © Springer-Verlag 2005.
UnivIS-Import:2015-03-09:Pub.2005.nat.dgeo.IGM.profes.triass
Keywords: Corals; End-Triassic mass extinction; Gastropods; Hochfelln; Northern Calcareous Alps; Silicification; Triassic/Jurassic transition